Climate change tripled heat-related deaths in early summer European heatwave - Clarke,B; Konstantinoudis,G; Barnes,C; Keeping,T; Otto,F; Gasparrini,A; Masselot,P; Mistry,M; Vicedo-Cabrera,A; Theokritoff,E (Grantham Institute, Imperial College London, 2025)
Human-caused climate change intensified the recent European heatwave and increased the number of heat deaths by about 1,500 in 12 European cities.Focusing on ten days of heat from June 23 to July 2, the researchers estimated the death toll using peer-reviewed methods and found climate change nearly tripled the number of heat-related deaths, with fossil fuel use having increased heatwave temperatures up to 4°C across the cities.They warn that heatwave temperatures will keep rising and future death tolls are likely to be higher, until the world largely stops burning oil, gas and coal and reaches net zero emissions. It is the first rapid study to estimate the number of deaths linked to climate change for a heatwave and was led by scientists at Imperial College London and the London School of Hygiene & Tropical Medicine.